1980
DOI: 10.1080/00223980.1980.9915156
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Situational Stress and Sex on Interpersonal Distance Preference

Abstract: The prediction that people prefer greater distance between themselves and others when they anticipate a stressful situation was tested. The sex of the "other" was expected to have an interactive effect on distance preference. Written descriptions of settings in which people anticipated future situations of high and low stress were presented and Ss indicated seating preference. When anticipating more stressful situations, more distance from another person was preferred. Males preferred to sit closer to the oppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
2
5
0
Order By: Relevance
“…This study provides several implications about personal distance. First, our experiment results show that the agents’ gender influenced personal distance, like in past studies [ 29 31 ] on the relationships between gender and personal distance in physical environments. Our study suggests that the gender of the approaching target has similar effects on personal distance regardless of the particular environment.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…This study provides several implications about personal distance. First, our experiment results show that the agents’ gender influenced personal distance, like in past studies [ 29 31 ] on the relationships between gender and personal distance in physical environments. Our study suggests that the gender of the approaching target has similar effects on personal distance regardless of the particular environment.…”
Section: Discussionsupporting
confidence: 81%
“…The results did not show any significant differences related to the participants’ gender factors, including the interaction effects (participants’ gender factor: p = 0.360, agents’ gender and participants’ gender factors: p = 0.167, type and participants’ gender factors: p = 0.914, coughing and participants’ gender factors: p = 0.130, agents’ gender, type and participants’ gender factors: p = 0.679, agents’ gender, coughing and participants’ gender factors: p = 0.264, type, coughing and participants’ gender factors: p = 0.275, type, agents’ gender, coughing and participants’ gender factors: p = 0.445). Therefore, the participants’ genders are insignificant as well as the reported results from the past studies [ 27 31 ].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Hence, in previous studies, both positive (Zajonc, 1965; Meglino, 1977) and negative (Jamal, 1984; Abramis, 1994) linear relationships were revealed between stress and performance. However, as C‐PMs are normally required to manage and control complicated construction projects involving demanding tasks, multi‐stakeholders, and adverse environments, previous stress management studies of construction professionals (Leung et al , 2005; Long et al , 1980; Sidman, 2005) have indicated that the relationships between stress and performance are mainly negatively linear (i.e. deterioration of performance resulting from increase in stress level) in the industry.…”
Section: Stress and Performancementioning
confidence: 99%